Estimating the difference in prevalence of common mental disorder diagnoses for Aboriginal and Torres Strait Islander peoples compared to the general Australian population. (21st June 2022) - Page, I. S.; Ferrari, A. J.; Slade, T.; Anderson, M.; Santomauro, D.; Diminic, S.
Abstract: Aims: There is currently little nationally representative diagnostic data available to quantify how many Aboriginal and Torres Strait Islander people may need a mental health service in any given year. Without such information, health service planners must rely on less direct indicators of need such as service utilisation. The aim of this paper is to provide a starting point by estimating the prevalence ratio of 12-month common mental disorders (i.e. mood and anxiety disorders) for Indigenous peoples compared to the general Australian population. Methods: Analysis of the four most recent Australian Indigenous and corresponding general population surveys was undertaken. Kessler-5 summary scores by 10-year age group were computed as weighted percentages with corresponding 95% confidence intervals. A series of meta-analyses were conducted to pool prevalence ratios of Indigenous to general population significant psychological distress by 10-year age groups. The proportion of respondents with self-reported clinician diagnoses of mental disorders was also extracted from the most recent survey iterations. Results: Indigenous Australians are estimated to have between 1.6 and 3.3 times the national prevalence of anxiety and mood disorders. Sensitivity analyses found that the prevalence ratios did not vary across age group or survey wave. Conclusions: To combat the current landscape of inequitable mental health in Australia, priority should be given to populations in need, such as Indigenous Australians. Having a clear idea of the current level of need for mental health services will allow planners to make informed decisions to ensure adequate services are available.